Features of the Clinical Course of Cystic Fibrosis in Children, Depending on the Type of Feeding (Czech Journal of Multidisciplinary Innovations, 2023)
The aim of the study was to assess the particular clinical course in children with cystic fibrosis depending on the type of feeding.